AN ANALYSIS OF TENSE AND ASPECT IN THE “TANGLED” MOVIE SCRIPT - Herani, Isti Endila; Rachmijati, Cynantia (IKIP Siliwangi, 2019)
This study is an attempt to analyze the tense and aspects found inside the ”Tangled” movie script. The data source is a sentence or speech the verb contains tense and aspects found on “Tangled” movie script. The study applied descriptive qualitative method.This study belongs to a descriptive research because it collects and analyzes the data, after that draws a conclusion based on the data. Then this research belongs to qualitative research because it involves analyzing and explaining the data. Additionally, this research is designed in descriptive qualitative research because the research examines the types of the language used of Tense and Aspects in